Association between periodontal condition and kidney dysfunction in Japanese adults: A cross‐sectional study. Issue 3 (11th August 2016) - Naruishi, Koji; Oishi, Keiji; Inagaki, Yuji; Horibe, Masumi; Bando, Mika; Ninomiya, Masami; Kawahara, Kazuhiko; Minakuchi, Jun; Kawashima, Shu; Shima, Kenji; Kido, Jun‐ichi; Nagata, Toshihiko
Abstract: Recent studies have demonstrated that chronic kidney disease (CKD) may be associated with the progression of periodontal disease. Diabetes mellitus (DM) is a major risk factor for CKD. The objective of this study was to clarify the relationship between periodontal condition and kidney dysfunction in patients who had kidney failure with or without DM. One hundred sixty‐four patients with kidney dysfunction were enrolled (male: N  = 105; female: N  = 59), and the relationship between periodontal condition and kidney dysfunction was analyzed in a cross‐sectional study. The subjects were divided into three groups: (a) patients with DM, (b) dialysis patients with nephropathy due to various kidney diseases, and (c) dialysis patient with nephropathy due to DM (diabetic nephropathy). Then, the effect of DM on the periodontal condition was analyzed. The patients were also stratified by CKD stage (into G1–G5) using the estimated glomerular filtration rate (eGFR), and the G5 group was divided in patients with or without DM. Correlations between eGFR and parameters of periodontal condition were calculated in patients from G1 to G4. The number of missing teeth was significantly higher in dialysis patients with diabetic nephropathy than in patients with DM, whereas alveolar bone loss did not show a significant difference among the three groups. In addition, the G5 patients with DM had a significantly higher number of missing teeth than the other CKD groups, whereas alveolar bone loss did not show a significant difference. In G5 patients with DM, Community Periodontal Index and Oral Hygiene Index scores were significantly higher than in G1‐4 patients with DM. There was a significant negative correlation between eGFR and the number of missing teeth. Patients with diabetic nephropathy have a higher rate of periodontal problems such as missing teeth in Japanese adults.